A prevalence survey of Wolbachia in butterflies from southern China. Issue 12 (12th October 2021) - Zhu, Dao‐Hong; Gao, Shuo
Abstract: Wolbachia is a maternally inherited endosymbiont of the phylum α‐Proteobacteria that is found widely in arthropods and nematodes. Wolbachia is the most common endosymbiont in butterflies (Lepidoptera) and it manipulates host reproduction mainly by inducing cytoplasmic incompatibility, male killing, and feminization. We studied the prevalence patterns of Wolbachia in 52 butterfly species from five families collected in southern China. A substantial infection incidence was determined in the study region, where 18 out of the 52 butterfly species (35%) were infected, including members of the families Hesperiidae, Lycaenidae, Nymphalidae, Papilionidae, and Pieridae. Based on multi‐locus sequence typing (MLST) and Wolbachia cell surface protein (WSP) profiles, seven unique sequence types (STs) and six wsp alleles were detected. One MLST haplotype was detected for the first time (ST‐wPcau). Most of the identified Wolbachia STs belonged to supergroup B, those found in two Ypthima spp. belonged to supergroup A. Many STs were shared among various insect species; the most widespread strain in our samples, ST‐41, was detected in seven butterfly species from four families. We discuss the potential horizontal transmission routes of Wolbachia, as well as the suitability of the Wolbachia strain typing method. Abstract : Wolbachia are maternally inherited endosymbiotic bacteria widely found in arthropods. We studied the presence of Wolbachia in 52 butterfly species from five families collected in southern China. A substantial infection incidence was determined: 35% of species were infected. Most Wolbachia strains identified were shared among various insect species; the most widespread strain, ST‐41, was detected in seven butterfly species from four families. We discuss the potential horizontal transmission routes of Wolbachia and the suitability of the Wolbachia strain typing method.